2016
DOI: 10.3390/ijerph13080768
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Consumption of Energy Drinks by a Group of Adolescent Athletes

Abstract: Background: Energy drinks (EDs) have become widely popular among young adults and, even more so, among adolescents. Increasingly, they are consumed by athletes, particularly those who have just begun their sporting career. Uncontrolled and high consumption of EDs, in addition to other sources of caffeine, may pose a threat to the health of young people. Hence, our objective was to analyze the consumption of EDs among teenagers engaged in sports, including quantity consumed, identification of factors influencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 41 publications
(75 reference statements)
1
23
0
Order By: Relevance
“…It has been showed that some adolescents consume EDs for their perceived physiological benefits without being aware of the potential health risks of these drinks (O'Dea, 2003). Similar to others (Maryam M. Nassaif, 2015;Musaiger & Zagzoog, 2013;Nowak & Jasionowski, 2016;Zucconi, 2013), 54% of EDs consumers in our study reported that the main reason for consuming EDs was its good taste. In contrast with another study, we found that 82% of the athletes didn't know that EDs contained caffeine and 20% believed that EDs contained vitamins (Musaiger & Zagzoog, 2013).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…It has been showed that some adolescents consume EDs for their perceived physiological benefits without being aware of the potential health risks of these drinks (O'Dea, 2003). Similar to others (Maryam M. Nassaif, 2015;Musaiger & Zagzoog, 2013;Nowak & Jasionowski, 2016;Zucconi, 2013), 54% of EDs consumers in our study reported that the main reason for consuming EDs was its good taste. In contrast with another study, we found that 82% of the athletes didn't know that EDs contained caffeine and 20% believed that EDs contained vitamins (Musaiger & Zagzoog, 2013).…”
Section: Discussionsupporting
confidence: 84%
“…This could be explained that athletes who sleep longer hours felt that they needed to drink EDs in order to feel energized for their sports activity. Nowak D. et al (Nowak & Jasionowski, 2016) showed that 28% of respondents claimed that EDs gave them a boost of energy. Similarly, our study showed that 19% of the athletes consumed the EDs to increase their energy and enhance their performance.…”
Section: Discussionmentioning
confidence: 99%
“…Among young Australian adults, AMED consumption ranged from 21.1% to 77% (Peacock et al, ; Pennay et al, ). In Europe, AMED consumption was reported by 3.4% of Slovakian adolescents (Holubcikova et al, ), 10.6% of Polish adolescent athletes (Nowak & Jasionowski, ), 20.6% of Dutch students (De Haan, de Haan, van der Palen, Olivier, & Verster, ), 39.0% of U.K. students (Johnson, Alford, Stewart, & Verster, ; Johnson, Alford, Verster, & Stewart, ), 44.4% of Italian students (Vitiello, Diolordi, Donini, & del Balzo, ), and 46.1% of Italian teenagers (Flotta et al, ). Among Brazilian students and teenagers, AMED consumption was reported by 12.9% to 31% (Bitancourt, Ribeiro Grilli Tissot, Marques Fidalgo, Fernandes Galdurόz, & da Silveira Filho, ; Eckschmidt, Guerra de Andrade, dos Santos, & Garcia de Oliviera, ; Locatelli, Sanchez, Opaleye, Carlini, & Noto, ), and 38% of Puerto Rican students reported AMED consumption (Cabezas‐Bou et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…41 Finally, a survey conducted in Poland showed that 29% of young athletes who reported consuming energy drinks reported a "health problem." 42 The current study sought to assess adverse events from energy drinks among a population-based sample of youth and young adults in Canada, including reports of seeking medical attention. Adverse events from coffee were also assessed for comparison, given that caffeine consumption from coffee has been used as the reference in risk assessments for energy drinks in Canada and elsewhere.…”
mentioning
confidence: 99%